Analisis disposisi matematis mahasiswa universitas Nurtanio Bandung melalui metode Video Based Learning (VBL) - Agustianti, Rifka; Simangunsong, Herlina (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
The low mathematical disposition of students is the background of this study. The aim is to analyze the mathematical disposition of students through a set of mathematical disposition scales using the Likert scale. 2 classes were taken as research samples through simple random sampling techniques. The research design used was Posttest-Only Control Design. The method used was the quasi-experimental method. The data analysis technique was descriptive statistics, then the Mann Whitney non-parametric test was carried out. A conclusion was obtained that the mathematical disposition of students with the application of the VBL method was better than the mathematical disposition of students with the application of the conventional method where the class with the VBL method showed a percentage of 76% in the moderate category and the class with the conventional method showed a percentage of 60% in the poor category.